Enseñanza de la Lengua de Señas Chilena en educación superior: percepciones sobre el uso de metodologías activas - González Moraga, Maribel (2025)
Chilean Sign Language (LSCh) was recognized a few years ago as the official language of the deaf community, as well as an essential part of its culture and identity (Law 21.303, 2021). However, there are still no linguistic policies that guide, through an official curriculum, its teaching either as a first or second language. LSCh is taught in higher education contexts; however, there is no evidence of the methodologies that are most effective for its teaching. The present study analyzes the effectiveness of the teaching and learning methodologies implemented in an LSCh workshop for 20 second year students of Special Education. The methodological approach used is action research with a mixed design. The data collection strategies included classroom observations and filming, a focus group and a student survey. The results indicate that active methodologies, in particular, Game-Based Learning, Flipped Classroom and Cooperative Learning together prove to be successful for LSCh learning, promoting motivation, participation and course involvement. We recommend extending the study to other LSCh teaching contexts.